Formation of Oxidatively Modified Lipids as the Basis for a Cellular Epilipidome - Spickett, Corinne M. (Frontiers in Endocrinology, 2020)
While often regarded as a subset of metabolomics, lipidomics can better be considered as a field in its own right. While the total number of lipid species in biology may not exceed the number of metabolites, they can be modified chemically and biochemically leading to an enormous diversity of derivatives, many of which retain the lipophilic properties of lipids and thus expand the lipidome greatly. Oxidative modification by radical oxygen species, either enzymatically or chemically, is one of the major mechanisms involved, although attack by non-radical oxidants also occurs. The modified lipids typically contain more oxygens in the form of hydroxyl, epoxide, carbonyl and carboxylic acid groups, and nitration, nitrosylation, halogenation or sulfation can also occur. This article provides a succinct overview of the types of species formed, the reactive compounds involved and the specific molecular sites that they react with, and the biochemical or chemical mechanisms involved. In many cases, these modifications reduce the stability of the lipid, and breakdown products are formed, which themselves have interesting properties such as the ability to reactive with other biomolecules. Publications on the biological effects of modified lipids are growing rapidly, supporting the concept that some of these biomolecules have potential signaling and regulatory effects. The question therefore arises whether modified lipids represent an “epilipidome”, analogous to the epigenetic modifications that can control gene expression.